Hubungan Asupan Makan, dan Pola Asuh Ibu dengan Kejadian Stunting Pada Balita di Puskesmas Kuala Bhee Kec.Woyla Induk Tahun 2024 - Nurul Alfata; Laila Apriani Hasanah Harahap; Wardah Iskandar; Sri Wahyuni Muhsin (STIKES Columbia Asia Medan, 2024)
Background: Stunting occurs when a child's height is lower than the average for age due to poor growth caused by chronic malnutrition, which occurs when a child's nutrient intake is inadequate for a long period of time. Stunting may have direct and indirect causes. Direct causes include inadequate nutrition, while indirect causes include parenting. Food consumption is a habit that improves the body's nutritional state in a measurable way. Objective: This study was to determine the relationship between food intake, and maternal parenting patterns with the incidence of stunting in toddlers at the Kuala Bhee Health Center, Woyla Induk District in 2024. Method: Quantitative, observational, cross-sectional techniques were used in this study. June to July 2024 were used for this study. Primary data and secondary data are two categories of data. Data were analyzed using the chi-square test for bivariate and univariate analysis. Results: The findings showed a significant correlation (p value = 0.000 <0.05) between food consumption and the incidence of stunting. P value = 0.002 <0.05, indicating a relationship between maternal parenting patterns and stunting incidence. Conclusion: There is a strong correlation between calorie consumption and stunting. Parental involvement is significantly associated with stunting rates. Suggestion: We hope that Posyandu cadres and Puskesmas officials at the study site will gain a deeper appreciation of the role played by parents in monitoring their toddlers' dietary needs.